Hermanski-Pudlak Syndrome with Cystic Fibrosis: A Case Report - Md Kamruzzaman, -; Halder, Kanta; Zaman, Ashikur; Akter, Gulshana (Dhaka Shishu (Children) Hospital Journal, 2021)
Abstract not available DS (Child) H J 2019; 35(1) : 74-76